Screen-type energy dissipator for small hydraulic structures - Zhu, Junfei. (2009)
Energy dissipators are commonly used in high velocity hydraulic engineering devices to dissipate hydraulic energy. Dissipators are used to in places where the excess energy could cause damage as scouring, erosion of tailwater channels, abrasion of hydraulic structures, or generation of tailwater waves. Hence, a comprehensive and intensive study about energy dissipators is of great important. The laboratory experiments shows that screens with a porosity of 40% could be used as energy dissipator effectively in small hydraulic structure, either as a single wall or a double wall. The experiments were carried out for a supercritical Froude number approximate from 6 to 17. The relative energy loss with screens was larger than classical hydraulic jump as predicted. Meanwhile, the relative energy loss can be increased 1% by receded 1cm tailgate depth. Thus the optimum tailgate depth happened when the tailgate is fully lowered. The study was compared with Rajaratnam and Hurtig’s (2000) study as well as Quek and Soh’s (2008) study. The relative energy loss was found to agree reasonably well with Rajaratnam and Hurtig’s (2000) results while only two flow patterns were accord with Rajaratnam and Hurtig’s (2000) study. By using experimental data with 2cm tailgate depth, the relative energy loss from present study is conforming to Quek and Soh’s (2008) study which is significantly lower than Rajaratnam and Hurtig’s (2000) study. This effect also demonstrates that relative energy loss decreasing with increasing tailgate depth.